Development and standardization of a COVID-19 Vaccination Anxiety scale for Adult Urban Indian Population (CVAS-A). Issue 5 (30th November 2022) - Khurana, Rati; Gupta, Lokesh; Kumar, Nimisha
ABSTRACT: Given the ongoing COVID-19 vaccination drive across the globe, a significant amount of confusion, mistrust, misunderstanding, and hesitancy had surfaced regarding the vaccine. A standardized tool to understand the possible reasons of COVID-19 vaccination anxiety and hesitancy would be valuable in this context. The current study aimed at developing a standardized tool to measure COVID-19 Vaccination Anxiety among Urban Indian adults. A 19-item scale was administered to an Urban adult Indian population (N = 760) between the period of February 2021- May 2021 to obtain factors associated with COVID-19 Vaccination Anxiety and establish reliability estimates of the scale. Infection-related anxiety, information-related anxiety and vaccine side-effect-related anxiety were the three factors determined through Factor Analysis. The scale was validated with Convergent and Discriminant Validity by finding correlation between the three factors of the scale and five factors of the Brief version of the Big-Five personality Inventory (extraversion, agreeableness, openness to experience, conscientiousness, and neuroticism). It is expected that a tool such as CVAS-A would help in understanding and managing COVID-19-related vaccination hesitancy.